Factors affecting the age at diagnosis of autism spectrum disorders in Nova Scotia, Canada. (March 2013) - Frenette, Priscilla; Dodds, Linda; MacPherson, Kathleen; Flowerdew, Gordon; Hennen, Brian; Bryson, Susan
While early diagnosis of autism spectrum disorders (ASD) is essential for ensuring timely access to early intervention services, there is limited existing literature investigating factors that delay this diagnosis. This population-based cohort study explored the age at which children in Nova Scotia, Canada, are diagnosed with ASDs and the factors associated with this age. Children diagnosed with an ASD between January 1992 and December 2005 were identified from a cohort of live births in the province between 1990 and 2002. Demographic and clinical variables were extracted from population-based perinatal and administrative health databases and evaluated as predictors of age at ASD diagnosis. Of 122, 759 live births, 884 cases of ASDs were identified during the study period. The median age at diagnosis within the cohort was 4.6 years. In adjusted linear regression analysis, a one year increase in maternal age at delivery was associated with a 0.06 decrease in age at ASD diagnosis ( p  = .0007). Children who were residents of Halifax County received their diagnoses 0.52 years later than residents of other counties ( p  = .0054). A diagnosis of attention-deficit/hyperactivity disorder (ADHD) was associated with a 1.29-year increase in age at diagnosis ( p  < .0001). These results suggest that potential exists for improving early detection of ASDs in the province. Future research in this field has the potential to contribute to our understanding of the causal pathways linking the demographic and clinical variables we have identified and the age at diagnosis of ASDs.